Pengaruh Dukungan Sosial Keluarga dan Religiusitas Terhadap Kesehatan Mental di SMKN 02 Kota Bengkulu - Mitra Mitra; Chardovan Rezu Anggara; Arif Dwi Prayoga (DAWUH : Islamic Communication Journal, 2024)
This research aims to see the influence of family social support and religiosity on the mental health of adolescents at SMK N 02 Bengkulu City. This research uses quantitative methods with data collection techniques in the form of distributing a questionnaire of 30 items. The sample studied was teenagers at SMK N 02, Bengkulu City. The data takers were 100 respondents. This research was analyzed using quantitative analysis using IBM SPSS statistics by testing correlation regression, normality test, reliability test and R square. Based on the results of this study, it shows that the influence of family social support and religiosity on the mental health of adolescents at SMK N 02, Bengkulu City is in the weak category, namely; 13.4%